Altered plasma marker of oxidative DNA damage and total antioxidant capacity in patients with Alzheimer\'s disease - Ameneh Moslemnezhad; Soleiman Mahjoub; Mehdi Moghadasi (Babol University of Medical Sciences, 2016)
Background: Recent studies have shown that oxidative stress (OS) is the most important indicator in the pathogenesis of Alzheimer's disease (AD), but the results in previous studies are conflicting. This study aimed to assess the plasma levels of 8-hydroxy-2'-deoxyguanosine (8-OHdG) as DNA oxidative damage marker and total antioxidant capacity (TAC) in patients with AD versus control group. Methods: Thirty patients with AD and 30 sex-and age-matched healthy subjects were studied. Diagnosis of AD was based on National Institute of Neurological and Communicative Disorders and Stroke and the Alzheimer's disease and Related Disorders Association (NINCDS/ADRDA) criteria. Also for the patients, Mini-Mental State Examination (MMSE), computed tomography (CT) scan and brain magnetic resonance imaging (MRI) were done. Plasma levels of 8-OHdG and TAC were measured by competitive ELISA method and ferric reducing antioxidant power (FRAP) assay, respectively. Results: Plasma levels of 8-OHdG was significantly higher in AD compared to control group (p<0.001), while the total antioxidant was significantly lower in patients compared to controls (p=0.002). The value of area under the ROC curve for 8-OHdG and TAC in discriminating AD from controls were 0.87 and 0.32, respectively. Conclusion: Our results indicate a link between oxidative stress and AD indicating a possible contributive role of these markers in the development of AD and as an indicator in the discrimination of AD from healthy controls.